Temporal and vertical variations in phythoplankton community structure and its relation to some morphometric parameters of four colombian reservoirs (2000)
Phytoplankton samples were taken at three depths within the photie zone of eaeh of four reservoirs, Punehiná, Las Playas, El Peñol and San Lorenzo loeated in Antioquia department, Colombia. A total of 77 taxa were identified in the four reservoirs. Diatoms were not included. In all reservoirs, Chlorophyta was the dominant group. Botryococcus braunii was the dominant species at Punchiná, Las Playas and El Peñol reservoirs; Cosmarium sp. was the dominant at San Lorenzo. Temporal variation in phytoplankton showed two peaks of abundance, apparently related to precipitation. Taxonomic composition among samples from the same reservoir showed little variation. Community structure at different depths showed significant differences only at San Lorenzo reservoir. The inverse of β-diversity showed small values indicating high similarity among the reservoirs. Diversitv showed no significant assoeiation with any morphometric factor evaluated (area, retention time, altitude and age).